2021
DOI: 10.1002/ccr3.3685
|View full text |Cite
|
Sign up to set email alerts
|

Renal failure and lung hemorrhage as a presentation of COVID‐19 infection, a case report

Abstract: The concurrent involvement of the lung and kidneys happens in COVID‐19 infection. The patient's respiratory symptoms resolved after hemodialysis. This finding raises the question that if hemodialysis can have a role in the treatment of COVID‐19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
1
0
Order By: Relevance
“…The concomitant involvement of the kidneys (AKI) and pulmonary involvement (pulmonary hemorrhage) after COVID-19 infection have been reported in case studies of adults with vasculitis, particularly necrotizing polyangiitis (5,6); however, none of the neonates had neurologic symptoms and did not show involvement of the kidneys or other organs.…”
Section: Discussionmentioning
confidence: 88%
“…The concomitant involvement of the kidneys (AKI) and pulmonary involvement (pulmonary hemorrhage) after COVID-19 infection have been reported in case studies of adults with vasculitis, particularly necrotizing polyangiitis (5,6); however, none of the neonates had neurologic symptoms and did not show involvement of the kidneys or other organs.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have been reported that progression of stages II and III of AKI results in poor prognosis and high mortality rate in patients with renal replacement therapy [ 13 ]. Therefore, the need for renal replacement therapy with AKI is an indicator of poor prognosis in a patient with COVID-19 pneumonia [ 14 ].…”
Section: Discussionmentioning
confidence: 99%